2006
DOI: 10.1016/j.ccr.2006.05.027
|View full text |Cite
|
Sign up to set email alerts
|

An Xpd mouse model for the combined xeroderma pigmentosum/Cockayne syndrome exhibiting both cancer predisposition and segmental progeria

Abstract: Inborn defects in nucleotide excision DNA repair (NER) can paradoxically result in elevated cancer incidence (xeroderma pigmentosum [XP]) or segmental progeria without cancer predisposition (Cockayne syndrome [CS] and trichothiodystrophy [TTD]). We report generation of a knockin mouse model for the combined disorder XPCS with a G602D-encoding mutation in the Xpd helicase gene. XPCS mice are the most skin cancer-prone NER model to date, and we postulate an unusual NER dysfunction that is likely responsible for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
91
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(101 citation statements)
references
References 55 publications
8
91
0
2
Order By: Relevance
“…[10][11][12] Recently we found that both human and mouse CS and TTD cells (and also cells from the rare combined disorder, XPCS) share a common defect in repair of oxidative lesions which might explain the overlapping progeroid features of these syndromes. 13 The idea that progeria in CS, TTD and XPCS is linked to accumulated endogenous DNA damage is further supported by genetic evidence: CS, TTD and XPCS mice additionally lacking a functional Xpa gene, which further reduces NER capacity, share common dramatic phenotypes including rapid postnatal onset of progeroid features and death around weaning. [13][14][15] We note that a number of other defects in CS and/or TTD cells and mice have been reported, namely defective transcriptional activation of nuclear hormone receptors (including regulators of fat metabolism) by the TFIIH complex.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…[10][11][12] Recently we found that both human and mouse CS and TTD cells (and also cells from the rare combined disorder, XPCS) share a common defect in repair of oxidative lesions which might explain the overlapping progeroid features of these syndromes. 13 The idea that progeria in CS, TTD and XPCS is linked to accumulated endogenous DNA damage is further supported by genetic evidence: CS, TTD and XPCS mice additionally lacking a functional Xpa gene, which further reduces NER capacity, share common dramatic phenotypes including rapid postnatal onset of progeroid features and death around weaning. [13][14][15] We note that a number of other defects in CS and/or TTD cells and mice have been reported, namely defective transcriptional activation of nuclear hormone receptors (including regulators of fat metabolism) by the TFIIH complex.…”
Section: Introductionmentioning
confidence: 99%
“…13 The idea that progeria in CS, TTD and XPCS is linked to accumulated endogenous DNA damage is further supported by genetic evidence: CS, TTD and XPCS mice additionally lacking a functional Xpa gene, which further reduces NER capacity, share common dramatic phenotypes including rapid postnatal onset of progeroid features and death around weaning. [13][14][15] We note that a number of other defects in CS and/or TTD cells and mice have been reported, namely defective transcriptional activation of nuclear hormone receptors (including regulators of fat metabolism) by the TFIIH complex. 16 However, the presence of these defects in different complementation groups of the same disease, or in both CS as well as TTD, and thus their ability to explain common disease symptoms, remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations